Robotics rehabilitation for assessment of activities of daily living (ADL) - Chee, P.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
Robotic Rehabilitation is a prominent rehabilitation tool that provides comprehensive repetitive tasks, diversity and feedback for cost efficiency with quantitative measurement of human motor performances substituting the conventional physiotherapy. However, the current literature has a paucity of robotic devices assessment on the human motor performances with different handedness. Therefore, this paper discusses the outcome of the study which investigated both hands kinematic abilities to accomplish a reaching task which is the virtual supermarket game (picking up the food) with their effect of handedness by using rehabilitation robotics device. Fifteen (15) subjects, 9 males, and 6 females are divided into different groups; males right-handed, males left-handed, female right-handed, female left-handed and males both-handed. From the study, it was found that the range of motion (ROM) was significantly dependent on the handedness. On the contrary, the game scoring was not affected by handedness. © 2016 IEEE.